Evaluation of user experience in augmented reality mobile applications - Davidavičienė, Vida; Raudeliūnienė, Jurgita; Viršilaitė, Rima (Journal of Business Economics and Management, 2021)
Globalization, technological development and a dynamic business environment influence the change of customer information demands. It becomes vital for organizations to find out the customer demand change and discover technological solutions to satisfy these demands. One of these technologies is augmented reality, which connects real and digital environments by expanding it with digitally coded information which is decoded by using a specific device. As this type of technology enables the changing information needs of customers to be met faster, organizations are increasingly using these technological solutions to achieve a variety of purposes: to position products innovatively, increase product awareness, create added value for the customer, increase sales. However, organizations often face the challenge of evaluating commercial augmented reality mobile applications in user experience. A two-case study has been selected to evaluate the user experience of augmented reality commercial mobile applications and provide recommendations for their development to address this issue. In this research, such methods as scoping scientific literature review, expert evaluation, and user experience questionnaire method were used. The study has identified the main factors influencing the positive user experience: the explicit purpose of the application, easy to use and learn, smooth operation, imaginative information presentation, and interactivity. First published online 29 December 2020